Digitalising products: towards an integrated view of challenges in development, design and user acceptance. (20th May 2019) - Belingheri, Paola; Neirotti, Paolo
Making products smarter and connected through digital technologies requires firms to combine a product-oriented logic with a service logic. The challenges of such a combination are manifold and we have just begun understanding how firms should deal with these challenges. The papers included in this special issue have recalled the attention on the importance of horizontal integration mechanisms in the product development process and of a balanced managerial attention on the product and the service-side of innovation. In the same way, a crucial role in determining the market success of smart connected products is played by design decisions aimed at increasing the level of usefulness and efficiency of smart connected products compared to established solutions. This requires firms' attention not only on the design choices for product functionalities, but also on the capability to influence the institutional framework (i.e., the sets of meanings, values, and managerial principles) that affects how products are used.